The Analysis of Collateral Revaluation in the Settlement of Problematic Murabahah Financing (Case Study: PT BPRS Haji Miskin Pandai Sikek) - Angraini, Anggita Tria; Devy , Tartila (The Future of Education Journal, 2025)
Murabahah financing is the financing with the most problem levels at PT BPRS Haji Miskin Pandai Sikek, so special attention is needed in the settlement process, for example reschuduling, but if the strategy has not been succesful then execution of collateral is carried out as the final step of settlement. Prior to this execution,colleteral reassessment (colleteral reassesment) was carried out because is was feared that collateral would change from the beginning to the end of the financing. This study uses a qualitative approach that is descriptive in nature, in this study outhor describes how the implementation and the constraints faced when carrying out collateral restitution at PT BPRS Haji Miskin Pandai Sikek. This guarantee breakdown should be carried out once every 6 months or when the customer’s collectibility descreases, not only when there are problem loans or when the guarantee is about to be executed.